PARTISIPASI PETANI DALAM KOMUNIKASI PENYULUHAN - Muhammad Alif (Metacommunication, 2018)
AbstarctThis study aims to determine the level of participation in the Farmers Group Source Murni in agricultural extension activities and find out the problems faced by the Farmers Group Source Murni in the activities of Agricultural extension communication in Ulin North Urban Village Subdistrict Ulin basin Banjarbaru City. In this study the data used are Primary data and Secondary data. Primary data for this research is obtained from direct interview with respondent farmer by using questionnaire. secondary data obtained from literature study And the relevant agencies or agencies. sampling taken with a total population of 28 farmers. Results and Discussion. The results of this research are the followings of the members of the farmer groups in lecture activities. The percentage of attendance is 3.45% because the respondent farmers feel that the implementation of Agricultural extension communication is not so interesting and less interesting delivery. Implementation of activities followed by members of farmer groups can be seen in the implementation of activities in demonstration activities with the frequency of presentation percentage of 55% because the farmers respondents feel that the implementation of agricultural extension through the demonstration of interesting delivery then affect the presence of farmers in following the extension. There are some problems commonly faced by farmers group of Sumber Murni in agricultural extension activities in Ulin Utara Urban Village that is less information from agricultural extension about the material given, time in giving less accurate in conducting counseling, less interesting discussion in the implementation counseling by extension workersKeywords: Participation, Communication Extension  Abstrak Penelitian ini bertujuan untuk mengetahui tingkat partisipasi pada Kelompok Tani Sumber Murni dalam kegiatan penyuluhan pertanian dan mengetahui permasalahan yang dihadapi Kelompok Tani Sumber Murni dalam kegiatan Komunikasi penyuluhan pertanian di Kelurahan Landasan Ulin Utara Kecamatan landasan Ulin Kota Banjarbaru.Pada penelitian ini data yang dipergunakan adalah data Primer dan data Sekunder.  Data primer untuk penelitian ini diperoleh dari hasil wawancara langsung dengan petani responden dengan menggunakan daftar pertanyaan. data sekunder diperoleh dari  studi kepustakaan Serta dinas atau instansi yang terkait. penarikan sampel di ambil dengan total populasi yakni sebanyak 28 petani.Hasil dan Pembahasan. Hasil dari penelitian ini adalah pelaksanaan yang di ikuti para anggota kelompok tani dalam kegiatan- kegiatan bersifat ceramah. Persentasi kehadirannya adalah 3.45 % dikarenakan petani responden merasa bahwa pelaksanaan Komunikasi penyuluhan pertanian tidak begitu menarik dan kurang menarik penyampaiannya.Pelaksanaan kegiatan yang di ikuti para anggota kelompok tani dapat dilihat dalam pelaksanaan kegiatan- kegiatan dalam kegiatan demontrasi dengan frekuensi persentasi kehadirannya 55 % dikarenakan petani responden merasa bahwa pelaksanaan penyuluhan pertanian melalui cara demonstrasi menarik penyampaiannya maka dari itu mempengaruhi kehadiran petani dalam mengikuti penyuluhan. Ada beberapa Permasalahan yang biasa dihadapi oleh kelompok tani Sumber Murni dalam kegiatan penyuluhan pertanian di Kelurahan Landasan Ulin Utara yakni, kurang lengkapnya informasi dari penyuluh pertanian tentang materi yang di berikan, waktu dalam memberika pnyuluhan yang kurang tepat dalam melaksanakan penyuluhan, kurang menarik pembahasan dalam pelaksanaan penyuluhan oleh penyuluhKata Kunci : Partisipasi, Komunikasi Penyuluhan,